Perancangan Strategi Sistem Informasi pada Yayasan Sosial SharingHappiness - Imannudin Akbar; Dena Susanti (In Search (Informatic, Science, Entrepreneur, Applied Art, Research, Humanism), 2021)
SharingHappiness is a foundation engaged in the social sector which currently only has a website-based platform. SharingHappiness has products, one of which is a fundraising campaign, where there are beneficiaries and donors or those who donate to the campaign. SharingHappiness uses third parties to advertise its products, one of which uses Facebook Ads. Advertising costs for these third parties increase as the total donations in a campaign increase so that the distribution of donations to the beneficiaries is less than optimal due to these advertising costs. That way, SharingHappiness wants to increase organic users, namely users who donate not from exposure to the ads they get so that advertising costs can decrease. SharingHappiness wants to improve the completeness of the platform they have in order to support the increase in organic users who donate so that advertising costs decrease. Therefore, IT/IS strategy planning is made using several analysis models so that the IT/IS used is in accordance with the needs. The analysis model for IT/IS planning at SharingHappiness Foundation uses PEST analysis, Porter's Five Forces, SWOT, BCG Matrix, Value Chain and McFarlan Grid.